Strategi Pemasaran Digital untuk Meningkatkan Jumlah Nasabah Tabungan SIMPEL Sesuai Etika Syariah (Studi Kasus pada Bank Muamalat Indonesia Cabang Pembantu Payakumbuh) - Khairina Khairina (ARZUSIN, 2026)
Research on marketing strategies in the Islamic banking sector has become a focus in various previous studies; however, research that specifically discusses the gap in the use of digital marketing to increase the number of Simpanan Pelajar (SimPel) savings customers remains limited. This study aims to analyze digital marketing strategies in increasing the number of SimPel savings customers in accordance with Islamic ethics at Bank Muamalat Indonesia, Payakumbuh Sub-Branch Office. This study employed a qualitative approach with a case study design. The research participants consisted of internal bank personnel and related parties selected through the purposive sampling technique. Data were collected through interviews, observation, and documentation and were then analyzed using thematic analysis and a SWOT approach. The results show that the marketing strategies implemented are still dominated by conventional methods, while the use of digital media remains very limited, thereby affecting the low number of SimPel savings customers. In addition, although the product has advantages based on sharia principles, marketing communication has not been able to reach the target market effectively. These findings contribute to the development of digital marketing and Islamic marketing studies and broaden understanding of marketing strategies in the Islamic banking sector. The conclusion of the study emphasizes the importance of integrating digital marketing and Islamic ethical values in improving marketing effectiveness. The practical implication is that banking institutions need to develop more innovative, ethical, and target-market-oriented digital promotion strategies for SimPel savings. Keywords: Digital Marketing; Islamic Banking; SimPel Savings; Marketing Strategy; Islamic Ethics.